Randomised controlled trial of a person-centred transition programme for adolescents with type 1 diabetes (STEPSTONES-DIAB): a study protocol - Philip Moons; Ewa-Lena Bratt; Anna Lena Brorsson; Anna Ek; Elisabeth Jelleryd; Torun Torbjörnsdotter; Carina Sparud-Lundin (BMJ Open)
Introduction Adolescence is a critical period for youths with chronic conditions, when they are supposed to take over the responsibility for their health. Type 1 diabetes (T1D) is one of the most common chronic conditions in childhood and inadequate self-management increases the risk of short-term and long-term complications. There is a lack of evidence regarding the effectiveness of transition programmes. As a part of the Swedish Transition Effects Project Supporting Teenagers with chrONic mEdical conditionS research programme, the objective of this study is to evaluate the effectiveness and experiences of different transitional care models, including a person-centred transition programme aiming to empower adolescents with T1D to become active partners in their health and care.Methods and analysis In this randomised controlled trial, patients are recruited from two paediatric diabetes clinics at the age of 16 years. Patients are randomly assigned to either the intervention group (n=70) where they will receive usual care plus the structured transition programme, or to the control group (n=70) where they will only receive usual care. Data will be collected at 16, 17 and 18.5 years of age. In a later stage, the intervention group will be compared with adolescents in a dedicated youth clinic in a third setting. The primary outcome is patient empowerment. Secondary outcomes include generic, diabetes-specific and transfer-specific variables.Ethics and dissemination The study has been approved by the Ethical Review Board in Stockholm (Dnr 2018/1725-31). Findings will be reported following the Consolidated Standards of Reporting Trials statement and disseminated in peer-reviewed journals and at international conferences.Trial registration number NCT03994536